2011
DOI: 10.3109/02699052.2011.597046
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of the Dysexecutive Questionnaire (DEX): Comparative data from non-clinician respondents—all raters are not equal

Abstract: (2011). Inter-rater reliability of the Dysexecutive Questionnaire (DEX): comparative data from non-clinician respondents -all raters are not equal. Brain Injury, 25 (10), 997-1004. Copyright and re-use policySee http://shura.shu.ac.uk/information.html Sheffield Hallam University Research Archivehttp://shura.shu.ac.ukInter-rater reliability of the Dysexecutive Questionnaire (DEX):Comparative data from non-clinician respondents -all raters are not equalKey Words: executive function, reliability, brain injury.2 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Affective instability indicated by inappropriate anger, impulsivity and risk-taking behavior are core features of BPD, and are also seen, to a lesser or greater degree, in neuropathological groups with executive dysfunction (Barker et al, 2010, 2011). Diminished inhibitory capacity increases the likelihood that individuals act on dominant and potentially maladaptive tendencies; in the case of individuals with BPD this may be self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…Affective instability indicated by inappropriate anger, impulsivity and risk-taking behavior are core features of BPD, and are also seen, to a lesser or greater degree, in neuropathological groups with executive dysfunction (Barker et al, 2010, 2011). Diminished inhibitory capacity increases the likelihood that individuals act on dominant and potentially maladaptive tendencies; in the case of individuals with BPD this may be self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…The only difference between the two versions is that DEX-S is written in the first person (i.e. 'I have difficulty thinking ahead and planning for the future') and DEX-I is written in the third person (i.e 'Has difficulty thinking ahead and planning for the future') Both versions are commonly used as part of the Behavioural Assessment of the Dysexecutive Syndrome (BADS) which is considered an ecologically valid multidimensional measure of executive functioning (Barker et al, 2011). DEX-I ratings are considered a more reliable index due to the tendency for patients to rate themselves with fewer or less problems (McBrinn et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The DEX-I has also been found to accurately identify 'real world' executive deficits and these measures corresponded with subsequent performance on BADS executive subtests (Wilson, 1996;. cited in Barker et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Other commonly used expert-rating scales assessing other constructs, such as the Hamilton Depression Rating Scale (Morriss, Leese, Chatwin, Baldwin, & Group, 2008) or the clinician-rated version of the Yale-Brown Obsessive Compulsive Scale (Goodman et al, 1989), have shown ICC of about .90. As for common EF self-and partner rating scales, the interrater reliability has generally been shown to be much weaker, for instance, .47 for the Dysexecutive Questionnaire (Barker, Morton, Morrison, & McGuire, 2011), between .62 and .72 for the Adult Executive Functioning Inventory (ADEXI; Holst & Thorell, 2018), and between .66 and .79 for the Barkley Deficits in Executive Functioning Scale (BDEFS; Barkley, 2011). However, EF interview measures, such as the Executive Interview, have been shown to have excellent (r ¼ .90) inter-rater reliability (Royall, Mahurin, & Gray, 1992).…”
Section: Reliability Of the Ec-10mentioning
confidence: 99%